Brain Function Network and Young Adult Smokers: A Graph Theory Analysis Study - Tan, Ying; Chen, Jing; Liao, Weiwei; Qian, Zhaoxin (Frontiers in Psychiatry, 2019)
Cigarette smoking is associated with abnormalities in widespread inter-regional functional connectivity of the brain. However, few studies focused on the abnormalities in topological organization of brain functional networks in young smokers. In the current study, the resting state functional magnetic resonance images were acquired from 30 young male smokers and 32 age-, gender- and education-matched healthy male nonsmokers. Functional network was constructed by calculating the Pearson correlation coefficients among 246 sub-regions in human Brainnetome Atlas. The topological parameters were compared between smokers and nonsmokers. The results showed that the functional network of both young smokers and nonsmokers had small-world topology. Compared with the nonsmokers, the young smokers exhibited decreased clustering coefficient and local network efficiency. Meanwhile, the clustering coefficient and local network efficiency were negatively correlated with duration of cigarette use. In addition, the increased nodal efficiency was mainly located in prefrontal cortex (PFC), cingulate gyrus, insular and caudate. Decreased connectivities among PFC, cingulate gyrus, insular, basal ganglia (which specific node) and thalamus were also observed. We revealed the abnormal topological organization of brain functional network in young smokers, which may improve our understanding of the neural mechanism of young smokers form brain functional network’ s topological organization level.